Love Others (2S): Psychoeducation to Increase Understanding of Bullying in Students at SMPN 16 Semarang - Aisyah; Dewi, Dinda Amalia; Setiyaji, Nanda Ridwan; Nada, Sania Qotrun; Asri, Adinda Ratu Kencana; Aini, Dewi Khurun (Fakultas Psikologi Universitas Pancasila, 2025)
The problem of bullying is rampant in education, especially in junior high schools. This research aims to educate students and raise awareness to prevent bullying. Based on the results of research at SMPN 16 Semarang, it was found that verbal bullying was rampant in the school environment. The form of community service implementation in this junior high school through bullying psychoeducation, has several stages, namely; an introduction, pre-test, material about bullying, post-test, declaration agreement (writing cartarsis and signatures), and consumption. The results showed that psychoeducation about bullying applied to students of class VIII-H SMPN 16 Semarang had a significant effect on increasing students' knowledge about bullying.